The functioning the global stock exchanges in the face of the global financial recession - Gruszczyńska-Brożbar, Elżbieta (Ekonomia i Prawo. Economics and Law, 2009)
After a stock market boom period between 2003 and 2007, falls caused by a world-wide pecuniary recession occurred on global markets. This article outlines the issue of the influence of the described crisis on the functioning of the oldest and biggest stock exchanges. Analytical attention was drawn to the changes of the basic activity indicators of stock exchanges in New York, London, Tokyo and Frankfurt on Main. The empirical data analysis made it possible to define the dynamics and dispersion of the changes.